INTEGRATION OF ECONOMIC AND INCLUSIVE COMMUNICATION APPROACHES IN CHILD LABOR ELIMINATION POLICIES IN WEST NUSA TENGGARA - Nizamudin; Evi Rosdiyanti; Ahmad (GEMOVE: Journal of Gender, Movement, and Empowerment, 2025)
This study examines the integration of economic approaches and inclusive communication in addressing child labor issues in West Nusa Tenggara (NTB) Province, Indonesia. Based on data from the August 2024 National Labor Force Survey (Sakernas), NTB has one of the highest child labor rates in Indonesia, with 19.15% of children aged 10-17 years engaged in economic activities. This research analyzes the socioeconomic factors driving child labor and evaluates the effectiveness of current policy interventions through an interdisciplinary framework combining economic analysis and inclusive communication strategies. The study employs a mixed-method approach, utilizing secondary data from Sakernas 2024 and document analysis of relevant policies. Results reveal that poverty, low parental education, rural residence, and cultural norms significantly contribute to child labor prevalence. The agricultural sector employs 45.36% of working children, predominantly as unpaid family workers (85.09%). Most working children (86.66%) continue schooling, indicating potential for intervention. The study proposes an integrated policy framework encompassing economic incentives including conditional cash transfers and social protection expansion, inclusive communication strategies engaging multiple stakeholders through culturally sensitive messaging, strengthened education access and quality, and enhanced labor inspection and enforcement mechanisms. This integrated approach addresses both structural economic constraints and socio-cultural dimensions, offering a comprehensive strategy for child labor elimination aligned with SDG targets. The findings provide actionable recommendations for policymakers to develop evidence-based interventions that protect children's rights while supporting family economic security.